Determinants of SEA effectiveness: an empirical investigation over municipal spatial planning in Sardinia - Andrea De Montis; Antonio Ledda; Amedeo Ganciu; Mario Barra; Simone Caschili (Journal of Agricultural Engineering, 2013)
The late formal tradition of strategic environmental assessment (SEA) European Directive into the Italian planning system has so far induced a variety of behaviour of administrative bodies and planning agencies involved. In Italy and Sardinia, a new approach to landscape planning is characterizing spatial planning practice from the regional to the municipal level. Currently municipalities are adjusting their master plan to the prescriptions of the regional landscape planning instrument (in Italian, Piano Paesaggistico Regionale, PPR), according to processes that have to be integrated with a proper SEA development. With respect to this background, the aim of this paper is to assess the level of SEA implementation on the master plans of Sardinia six years after the approval of the PPR. The first results show that many municipalities are not provided with a master plan (in Italian, Piano Urbanistico Comunale, PUC) and they have in force just an old planning tool. Moreover, just some municipalities have adapted the PUC to the PPR carrying out a SEA process.